PWE-397 What is the correct prophylactic dose of tinzaparin in general surgical patients?. (22nd June 2015) - El-Sayed, C; Francombe, J
Abstract : Introduction: Thrombophylaxis should be prescribed in accordance with risk of thrombosis. The manufacturers of Tinzaparin recommend 3500 units for prophylaxis of DVT in all general surgical patients. Orthopaedic patients are classified as high risk and should receive a weight based calculated dose of 50 IU/kg body or 4500 units. Currently there is no consideration of tinzaparin dose for general surgical patients who are at high risk of thrombosis i.e. cancer patients or emergency surgery patients. Furthermore, there is no guidance for patients who are under or overweight. Method: A prospective audit was conducted over 8 weeks on one ward. All emergency and elective surgical patients were considered. Data collected included patients' demographics, weight and tinzaparin dose. This was compared to a theoretical weight calculated dose (TWCD). Results: 100 general surgical patients were included. Median age 69 years (25–95). Median weight 74 Kg (41–100). 30% of patients underwent surgery and were considered high risk of DVT. 70% were managed conservatively and considered low risk. 13% of patients received 3500 units. 87% received 4500 units. 57% of general surgical patients received too high a dose of tinzaparin on risk criteria alone by 1000 units. Median TWCD 3650 units (2095 -6487). All high risk patients received the recommended 4500 units. Median TWCD 3640 units (2750- 4800). Considering TWCD; 71.2% patients were over anti-coagulated by median 1109 units. 20.7% of overweight patients were under anti-coagulated by median 1560 units. Four patients bled significantly post surgery. They received 4500 units. According to weight based calculations they were over anti-coagulated by a median of 638 units. Conclusion: The correct dose of tinzaparin needs clarification in general surgical patients. We recommend consideration of a weight calculated dose of tinzaparin. Disclosure of interest: None Declared.